"I just re-evaluated what was beautiful when I went through treatment:" an analysis of Elly Mayday's ovarian cancer narrative. Issue 8 (17th November 2022) - Tetteh, Dinah A.
ABSTRACT: This study examines how the ovarian cancer narrative of Canadian model and body-positive advocate, Elly Mayday, disrupted and also intervened in discourses about ovarian cancer, celebrity cancer experiences, and representation of the diseased female body. My textual analysis revealed that Elly's narrative expanded available representations of celebrities who have been diagnosed and treated for ovarian cancer and the varied ways the cancer-afflicted female body can be embodied. However, Elly also pushed the boundaries on conventional views about celebrity cancer narratives and representation of the diseased female body by publicly and visually celebrating her scarred body and other intimate aspects of her experience often unavailable in mainstream celebrity cancer narratives, including hair loss, infertility, and candid reflections on side effects of treatments. Implications of the findings for ovarian cancer scholarship and feminist theory and research are discussed.